Book Reviews (Rev. Anal. Numér. Théor. Approx., 2001)
Book reviews for:Stephen J. Wright, Primal-dual interior-point methods, SIAM, Philadelphia, 1997, ISBN 0-89871–382-X, xv + 289 pp. Reviewed by A. Curseu.Desmond J. Higham and Nicholas J. Higham, Matlab Guide, SIAM, Philadelphia, 2000, ISBN 0-89871-469-9, xxii + 283 pp. Reviewed by E. Catinas.A. Griewank, Evaluating  Derivatives.  Principles  and  Techniques  of  Algorithmic  Differentiation, Frontiers in Applied Mathematics Series no.19, SIAM, Philadelphia, 2000, ISBN 0-89871-451-6, xxiv + 369 pp. Reviewed by E. Catinas.C. Meyer, Matrix Analysis and Applied Linear Algebra, SIAM, Philadelphia, 2000, ISBN 0-89871-454-0, xii + 718 pp., Solutions Manual 171pp + CD. Reviewed by E. Catinas.